KONSEP HUBUNGAN TOTAL (TOTAL RELATIONSHIP CONCEPT) DALAM PEMBERIAN KREDIT OLEH BANK KEPADA NASABAH - Marcellino Mukti Prabowo (Fakultas Hukum Universitas Udayana, 2024)
This research aims to analyze and explain the concept of total relationship agreement in providing credit. With the background of Bank Mandiri's policy in letter no. 033/SPb/MTF/VI/2023 this article was written to analyze the correlation of the Total Relationship Agreement concept with this policy and to analyze whether the use of the Total Relationship Agreement concept in Bank Mandiri's policy is in accordance with credit grant approval procedures or not yet. By using normative juridical research methods based on Law no. 7 of 1992 concerning Banking as amended several times, most recently by Law no. 4 of 2023 concerning Development and Strengthening of the Financial Sector and OJK Regulation no. 42/POJK.03/2017 concerning the Obligation to Prepare and Implement Bank Credit or Financing Policies for Commercial Banks, it was found that the Total Relationship Agreement concept in Bank Mandiri policy No. 033/SPb/MTF/VI/2023 was carried out to analyze the ability to pay credit applicants based on the debt conditions of the company where the prospective credit applicant works. With the issuance of Bank Mandiri policy no. 033/SPb/MTF/VI/2023 resulted in an analysis of approval for granting credit that was not in accordance with the procedures and procedures for analyzing approval for granting credit. The bank's confidence in the credit applicant's ability to pay credit must be achieved by analyzing credit approval methods. Analysis of approval for granting credit must be assessed objectively and in depth and based on the completeness of the credit applicant's files and information. With an analysis of approval for granting credit that is not based on existing assessment procedures, the analysis of approval for granting credit will have the potential to be an analysis that is not objective and in-depth.